Re-imagining classrooms as spaces for learning and professional development of teachers and teacher educators - Takker, Shikha; Khunyakari, Ritesh (Voices of Teachers and Teacher Educators, 2015)
In this article, we identify the potential areas of support required by teachers while teaching in the classroom. We discuss two classroom episodes where the teacher educators did not engage with the struggles of the teacher and the demands of the teaching situation. The lack of support from teacher educators and persistence in routinising classroom observations, has refrained teachers and teacher educators in utilising the potential of classrooms as spaces for learning of all. An exploration into the beliefs of teacher educators indicates that they overlook critical aspects of teaching and learning when observing classroom teaching. We conclude by suggesting possible ways in which teachers and teacher educators can collaborate by reflectively engaging with learning opportunities arising from classrooms.